Tibial Tray with a Stem: Does It Have Any Role in Primary Cemented Total Knee Replacement? - Samy, Ahmed M.; Azzam, Wael (The Journal of Knee Surgery, 2020)
Over many decades, total knee replacement (TKR) has become the ideal treatment option for advanced arthritis. Many designs were introduced to increase the stability of the tibial tray, hence the longevity of the prosthesis. This retrospective study was performed on 168 patients who received NexGen cemented primary total knee either with standard tibial tray (group A) or tibial tray with an intramedullary stem (group B) between May 2008 and May 2017. We reviewed all preoperative and postoperative clinical and radiological data retrospectively. In addition, a prospective clinical and radiological reassessment was done. Our aim was to answer the following questions: (1) Is there any difference between both groups in regard to clinical and radiological results? (2) Is there any difference in the revision rate? (3) Is there a role of using stemmed tibial tray in primary TKR? Better results were recorded in obese and severely obese patients having stemmed cemented tibial tray and so for patients with marked and severe preoperative varus angle. Our recommendations are to use cemented tibial tray with a stem in complicated primary surgery without fear of adverse effects on short and intermediate terms of follow-up.
Keywords: knee replacement; stemmed tibial tray; varus